2013
DOI: 10.1682/jrrd.2012.06.0119
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between cognition and gait performance in older adults receiving physical therapy interventions in the home

Abstract: Abstract-Persons undergoing physical therapy home services often have difficulty with mobility and gait. The purpose of this study was to determine whether there was a relationship between gait and a rating of cognitive functioning in persons undergoing home-care physical therapy services. Patients over the age of 65 (n = 11,601) seen by a home-care agency between 2007 and 2008 were included in the retrospective analysis, and 10,953 (mean +/-standard deviation age 83.2 +/-7.1; 31%) met the criteria of being ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“… 24 Although physical and mental function decrease with aging, the coexistence of DM and diabetic complications could accelerate the process or make the physical and mental conditions even worse. 28 Previous studies have shown that both declining physical 29 and cognitive function 30 might affect balance function. Pijpers 7 found risk factors that partly increase fall incidents in older diabetic patients included limitations in ADLs, impaired physical performance (including balance and gait), and cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“… 24 Although physical and mental function decrease with aging, the coexistence of DM and diabetic complications could accelerate the process or make the physical and mental conditions even worse. 28 Previous studies have shown that both declining physical 29 and cognitive function 30 might affect balance function. Pijpers 7 found risk factors that partly increase fall incidents in older diabetic patients included limitations in ADLs, impaired physical performance (including balance and gait), and cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…The Safe Strides plus Zōntago program resulted in better overall functional changes at the end of the episode of care. The Safe Strides program has already been shown to improve patient outcomes in a large cohort of persons with mixed diagnoses, 5,6 yet the Safe Strides plus Zōntago program was more effective in demonstrating ADL changes over the older adult's course of care. Time spent with the patients was similar.…”
Section: Discussionmentioning
confidence: 99%
“…There is emerging evidence that older adults benefit from rehabilitative services after discharge from the hospital via exercise programs. [1][2][3][4][5][6][7][8] Strength and balance interventions in the home have resulted in functional changes in persons post stroke, with heart failure, at fall risk, and other disorders. 2,3,6,7 Functional status is a strong predictor of readmission rates in persons discharged from inpatient rehabilitation based on over 4,000,000 inpatient rehab admissions.…”
Section: Introductionmentioning
confidence: 99%